Nuclear Condensation of CDYL Links Histone Crotonylation and Cystogenesis in Autosomal Dominant Polycystic Kidney Disease. Issue 9 (September 2022) - Dang, Lin; Cao, Xinyi; Zhang, Tianye; Sun, Yongzhan; Tian, Shanshan; Gong, Tianyu; Xiong, Hui; Cao, Peipei; Li, Yuhao; Yu, Shengqiang; Yang, Li; Zhang, Lirong; et al.
Significance Statement: Recent studies support a critical role of epigenetics in cyst-associated gene expression and the progression of autosomal dominant polycystic kidney disease (ADPKD), although the underlying molecular mechanisms remain elusive. Here, we show that expression of CDYL, a chromodomain Y-like transcription repressor and crotonyl-CoA hydratase, is suppressed in ADPKD kidneys, accompanied by an increase of histone lysine crotonylation (Kcr). Interestingly, CDYL can form biomolecular condensates, which enhance its catalytic activity on histone Kcr. Through a phase separation–mediated mechanism, overexpression of CDYL reduces histone Kcr, inhibits the expression of cyst-associated genes, and slows cyst growth. Thus, our study establishes a prominent role for CDYL nuclear condensation in regulating histone Kcr, the cyst-associated gene expression program, and ADPKD progression. Visual Abstract: Abstract : Background: Emerging evidence indicates that epigenetic modulation of gene expression plays a key role in the progression of autosomal dominant polycystic kidney disease (ADPKD). However, the molecular basis for how the altered epigenome modulates transcriptional responses, and thereby disease progression in ADPKD, remains largely unknown. Methods: Kidneys from control and ADPKD mice were examined for the expression of CDYL and histone acylations. CDYL expression and its correlation with disease severity were analyzed in a cohort of patients with ADPKD. Cdyl transgenic mice were crossed with Pkd1 knockout mice to explore CDYL's role in ADPKD progression. Integrated cistromic and transcriptomic analyses were performed to identify direct CDYL target genes. High-sensitivity mass spectrometry analyses were undertaken to characterize CDYL-regulated histone lysine crotonylations (Kcr). Biochemical analysis and zebrafish models were used for investigating CDYL phase separation. Results: CDYL was downregulated in ADPKD kidneys, accompanied by an increase of histone Kcr. Genetic overexpression of Cdyl reduced histone Kcr and slowed cyst growth. We identified CDYL-regulated cyst-associated genes, whose downregulation depended on CDYL-mediated suppression of histone Kcr. CDYL assembled nuclear condensates through liquid-liquid phase separation in cultured kidney epithelial cells and in normal kidney tissues. The phase-separating capacity of CDYL was required for efficient suppression of locus-specific histone Kcr, of expression of its target genes, and of cyst growth. Conclusions: These results elucidate a mechanism by which CDYL nuclear condensation links histone Kcr to transcriptional responses and cystogenesis in ADPKD.